2010
DOI: 10.1055/s-0029-1245772
|View full text |Cite
|
Sign up to set email alerts
|

Selbstverletzendes Verhalten und komorbide psychische Störungen: ein Überblick

Abstract: Depressive disorders and the borderline personality disorders are robustly associated with NSSI. It is still unknown whether or not the occurrence of NSSI with particular disorders can be explained by comorbidity with the borderline syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 31 publications
2
25
0
7
Order By: Relevance
“…Findings suggest that NSSI is comorbid with a wide range of diagnoses. The most common comorbid diagnoses were major depression, PTSD, and social phobia, supporting the results of others [13, 21] and a review by Nitkowski and Petermann [48]. Results are also in line with the chart review of inpatient adults with NSSI [15], characterized by high rates of internalizing disorders like depressive and anxiety disorders.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Findings suggest that NSSI is comorbid with a wide range of diagnoses. The most common comorbid diagnoses were major depression, PTSD, and social phobia, supporting the results of others [13, 21] and a review by Nitkowski and Petermann [48]. Results are also in line with the chart review of inpatient adults with NSSI [15], characterized by high rates of internalizing disorders like depressive and anxiety disorders.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding of a prevalence rate of 20% of adolescents with NSSI disorder also fulfilling diagnostic criteria for BPD corresponds to some studies [24, 48, 49] but is lower than the rate of 50% reported by Nock et al [13]. On the criteria level, adolescents with NSSI disorder without a comorbid BPD endorsed a mean of 2.3 borderline symptoms compared with a mean of 0.3 endorsed by the clinical control adolescents.…”
Section: Discussionsupporting
confidence: 82%
“…In adolescent psychiatric samples, prevalence rates of NSSI have found to be as high as 60% for one incident of NSSI and around 50% for repetitive NSSI [8]. NSSI not only can occur in the broad context of psychiatric disorders (affective disorders, BPD, substance abuse, anxiety disorder, posttraumatic stress disorders) but can also occur without comorbid psychiatric diagnosis [911]. To date, only few studies on the longitudinal development of NSSI exist.…”
Section: Epidemiologymentioning
confidence: 99%
“…NSSI is comorbid with several mental disorders (In‐Albon et al, ), especially mood disorders, anxiety, substance abuse disorders, and externalizing disorders (Nitkowski & Petermann, ). In addition, the relationship between NSSI, eating disorders, and borderline personality disorder (BPD) has been well documented: Some studies have found that between 25.4% and 55.2% of eating disorder patients report NSSI (Claes et al, ; Claes, Vandereycken, & Vertommen, ), and have reported a relationship between body image dissatisfaction and NSSI (Pérez et al, ).…”
Section: Introductionmentioning
confidence: 99%